Mastering Conversational AI: An In-depth Review of Recent Developments - Krishna, Dr. Tiruveedula Gopi; Srieenivas, Dr. Nune; Reddy, Dr. Chandra Sekhar; Abebe, Dr. Teklu Urgessa; Rathee, Dr. Davinder Sing; Mahboub, Dr. Mohamed Abdeldaiem Abdelhadi (Mastering Conversational AI: An In-depth Review of Recent Developments, Edition 1, 2025)
Unlock the full potential of Conversational AI with this comprehensive review, designed for developers, conversation designers, product owners, project managers, software developers, data scientists, and anyone interested in harnessing the power of AI-driven chatbots. This book provides a step-by-step approach to mastering Conversational AI, from selecting the right AI assistant to developing engaging conversations and creating solid chatbots that can handle routine client inquiries. Discover how to train classifiers from scratch, how to build question/answer bots and then evaluate error frequency to build a plan. Learn how to get started with conversational AI, as well as how to create advanced chatbots that redefine the customer experience of businesses. Since the emergence of ChatGPT it is relevant to offer an introduction to Natural Language Processing (NLP) and machine learning (ML) assistance in code form. Discuss AI in SW development, and get useful tips to apply Conversational AI in the perceptive code programs. This book is recommended to all marketers, lawyers, doctors and teachers, software developers, business people and the common population interested in this new technology. Within the framework of this review, you will be ready to create conversational AI aids that function and change the existing interaction with clients and customers for the better.